ANALYSIS AND MANUFACTURING OF CHILDREN PLAYING TOOL IN KINDERGARTEN SCHOOL - Wiyogo; Galfri Siswandi (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
The making of children's play equipment is in the form of a set of tools where the playground has the benefits of training early childhood motor skills. The implementation of the activity was carried out in the Kindergarten Pembina Jekan Raya District, Palangka Raya as a partner. The purpose of community service activities carried out in tertiary institutions is in line with the functions and objectives mandated in Law Number 12 of 2012, Article 4 paragraph 3; "Developing Science and Technology by paying attention and applying the value of Humanities". And in article 5, paragraph 4; "The realization of Community Service based on reasoning and research work that is useful in advancing public welfare and intellectual life of the nation". The method used is to analyze the needs of partners related to the availability of play tools, determine the design of tools to be made and prepare tools and materials used in making play tools and measure the index of perception of the teacher and parents of students. From the measurement results, it was found that the index value of the instrument was based on the calculation of the perception of the teacher and parents of students reaching 94.83% which can be concluded that the respondent was "very good / very agree".